Phoenician Furniture: A Typology Based on Iron Age Representations from the Eastern and Western Mediterranean Area (c. 1200-300 B. С.) - Gubel, Eric (1983)
Ph.D. Dissertation; Supervisor: Denyse Homès-Fredericq; in print; will be published as Studia Phoenicia VI: Phoenician Furniture. A Typology based on Iron Age Representations with Special Reference to the Iconographie Background; ca. 360 p., 70 fig., 37 pl. The book contains